2021
DOI: 10.1021/acs.jpclett.1c01393
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Gallium Oxide Monolayer for Gas-Sensing Application

Abstract: A two-dimensional (2D) Ga 2 O 3 monolayer with an asymmetric quintuple-layer configuration was reported as a novel 2D material with excellent stability and strain tunability. This unusual asymmetrical structure opens up new possibilities for improving the selectivity and sensitivity of gas sensors by using selected surface orientations. In this study, the surface adsorptions of nine molecular gases, namely, O 2 , CO 2 , CO, SO 2 , NO 2 , H 2 S, NO, NH 3 , and H 2 O, on the 2D Ga 2 O 3 monolayer are systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Recently, two van der Waals 2D ferroelectric (FE) configurations of Ga 2 O 3 were discovered in our previous studies [24,25] by adopting a class of stable single-layer configurations based on III 2 -VI 3 compounds [26][27][28][29] with an asymmetric quintuple-atomic-layer configuration. One Ga 2 O 3 layer consists of five triangular atomic lattices stacked in the sequence O-Ga-O-Ga-O and belongs to the R3m space group (No.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two van der Waals 2D ferroelectric (FE) configurations of Ga 2 O 3 were discovered in our previous studies [24,25] by adopting a class of stable single-layer configurations based on III 2 -VI 3 compounds [26][27][28][29] with an asymmetric quintuple-atomic-layer configuration. One Ga 2 O 3 layer consists of five triangular atomic lattices stacked in the sequence O-Ga-O-Ga-O and belongs to the R3m space group (No.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies [37][38][39] revealed a metastable configuration of 2D vdW Ga 2 O 3 monolayer with intrinsic dipole pointing from top to bottom surfaces (i.e., from negatively to positively charged centers). The structure is analogous to ferroelectric zinc blende (FE-ZB ) phase of III 2 −VI 3 compounds [32,40], as shown in Supporting Information Figure S1.…”
Section: Introductionmentioning
confidence: 93%
“…8 CO x (the sum of CO and CO 2 ) electrical sensors operate through the changes in the current or voltage in materials. Such changes in material conductivity occur by charge transfer (CT) between the sensor material and the target gases 9,10 via gassensor chemical interaction. To date, many CO x gas sensors have been designed for gas sensing technologies, yet they are restricted by high operating temperature, insufficient sensitivity, and expensiveness.…”
Section: Introductionmentioning
confidence: 99%